2022
DOI: 10.1155/2022/1890823
|View full text |Cite|
|
Sign up to set email alerts
|

NEK2 Serves as a Novel Biomarker and Enhances the Tumorigenicity of Clear-CellRenal-Cell Carcinoma by Activating WNT/β-Catenin Pathway

Abstract: Objective. Currently, cumulative evidence has shown that loss of NEK2 function suppresses tumor growth. However, complete studies on the regulatory role of NEK2 in clear-cellrenal-cell carcinoma (ccRCC) are rarely reported. Methods. The GEPIA database was used for information mining to analyze the gene expression differences between ccRCC tumor and normal tissues. At the same time, we analyzed the protein expression of NEK2 in clinical ccRCC samples and ccRCC cell lines. We detected the effect of NEK2 on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, Nek2 induced osteoclast differentiation and bone destruction via heparanase in multiple myeloma (38). Nek2 has been reported to plays an important regulatory role in MAPK (39,40), Wnt/β-Catenin pathway (41)(42)(43), PI3K/Akt pathway (44), and other pathways. Experimental evidence suggested that troponin-associated protein (Troap) played a key role in regulating cell proliferation in multiple tumors (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nek2 induced osteoclast differentiation and bone destruction via heparanase in multiple myeloma (38). Nek2 has been reported to plays an important regulatory role in MAPK (39,40), Wnt/β-Catenin pathway (41)(42)(43), PI3K/Akt pathway (44), and other pathways. Experimental evidence suggested that troponin-associated protein (Troap) played a key role in regulating cell proliferation in multiple tumors (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nek2 induced osteoclast differentiation and bone destruction via heparanase in multiple myeloma 43 . Nek2 has been reported to play an important regulatory role in MAPK 44 , 45 , Wnt/β-catenin 46 48 , PI3K/Akt 49 , and other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Furthermore, the study performed by Zhou et al, shown that NEK2 enhances the potential of renal-cell carcinoma cells to proliferate, migrate, and invade by triggering the Wnt/beta-catenin signaling pathway. 48 Studies has indicated that in 60% of adult AML patient samples, BIRC5 expression is detected. Complex cytogenetic aberrations in adult AML patients were associated with high expression of BIRC5 .…”
Section: Discussionmentioning
confidence: 99%